Pengaruh Model Pembelajaran Student Facilitator and Explaining terhadap Kemampuan Berpikir Kritis Matematis Siswa Ditinjau dari Kemandirian Belajar - Alimuddin, Alimuddin; Sahid, Sahid; Musdalifah, Musdalifah (Issues in Mathematics Education (IMED), 2024)
This study aims to determine the effect of Student Facilitator and Explaining (SFAE) learning model on students' mathematical critical thinking skills in terms of learning independence. This research is a quantitative research with a quasi experimental research in form of posttest only control roup design. The population are students in grade X MIPA in two SMA in Takalar with the number of students is 363. The samples are students in two different class from two different schools that chosen by using cluster random sampling technique. The data were collected by observation sheets, test, and questionnaire. The data analyzed using descriptive and inferential statistical analysis. The results of analysis showed that: (1) average of test score of students taught with SFAE learning model was higher than score obtained by students in control group, (2) in terms of learning independence, average of test score of students taught with SFAE learning model was higher than score obtained by students in control group, (3) there is an interaction between students' mathematical critical thinking skills and learning independence. Based on the results of analysis, there is an effect of SFAE learning model on students' mathematical critical thinking skills in terms of learning independence.